2019
DOI: 10.3390/jfmk4010005
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Dental Malocclusion and Neuromotor Control in Young Healthy Subjects through New Evaluation Tools

Abstract: The presence of a correlation between stomatognathic and postural systems has been investigated by different authors trying to identify a possible influence of dental occlusion on body posture and balance. The aim of this study was to evaluate the relationship between dental occlusion and neuromuscular control in a healthy young population using modern evaluation tools. 25 subjects (9 males and 16 females, aged 23 to 44) were evaluated for dental occlusion, particularly in relation to overjet and overbite para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Significances can be recorded for individual parameters with angle class II malocclusion playing a role. The craniomandibular system can generate compensations which may initially be limited to the head/neck area, but this altered head posture consequently results in causing small imbalances in posture [16,19]. Scharnweber et al [13] also refuted a connection between dental malpositions and postural control in men (18-35 years) and explained this by compensation mechanisms of the body.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Significances can be recorded for individual parameters with angle class II malocclusion playing a role. The craniomandibular system can generate compensations which may initially be limited to the head/neck area, but this altered head posture consequently results in causing small imbalances in posture [16,19]. Scharnweber et al [13] also refuted a connection between dental malpositions and postural control in men (18-35 years) and explained this by compensation mechanisms of the body.…”
Section: Discussionmentioning
confidence: 99%
“…Possible correlations between dental parameters and postural control are also discussed in literature [13,14,16,19,21,22]. Accordingly, Perinetti et al [16] found some weak correlations between malocclusions and postural control; the overbite showed correlations with anterior-posterior and lateral fluctuations [16].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…According to this study, there is no evidence between occlusal and postural characteristics, and it is clear that the presence of pain in the TMJ is not connected to the existence of a demonstrable occluded-postural anomaly, therefore, the use of tools and techniques for measuring presumed occlusal abnormalities (electromyography, kinesiography, posturography, etc.) cannot be justified in evidence-based medicine [1][2][3][4][5][6]. Stomatognathic systems perform different roles, such as in breathing, as can be summarized with some concepts.…”
mentioning
confidence: 99%